Reproductive performance of Sirohi goats and its crosses with Beetal in Semi arid condition of Rajasthan - Swami, P D; Barhat, N K; Joshp, R K; Murdia, C K; Kumar, Vijay (The Indian Journal of Animal Sciences, 2011)
The effect of genetic and non-genetic factors on reproductive performance of Sirohi and its crosses with Beetal (halfbred) in semi arid condition in Rajasthan was studied. The crossbred had significantly less kidding interval (KI) than Sirohi does. There was no effect of season on reproductive traits studied. However, other factors influence the reproductive traits significantly. The regression of dam’s weight at conception on gestation length (GL) and age at first kidding (AFK) was significant.